Hemp-lime composite for buildings insulation: material properties and regulatory framework - Rosa Agliata (Vitruvio: International Journal of Architectural Technology and Sustainability, 2019)
The increasing demand for indoor comfort in housing sector, together with the development of environmental awareness by people and societies, is leading to a rising need of new construction materials. Research and industries are then developing materials capable of meeting environmental and technical requirements: made from renewable sources; based on natural compounds to ensure healthy indoor environment and safe disposal; having good insulation properties, especially for energy saving. A material showing these features is the hemp-lime biocomposite, a natural-based mixture made of a lime binder matrix and shives aggregate, in different proportions. This paper wants to present an overview of the most interesting material properties for the building sector and a brief regulatory framework, in order to highlight the advantages that the use of this composite for building envelopes and internal partitions may provide.